Issues in food security in Jamaica - Davies, Omar (National Food and Nutrition Coordinating Committee ofJamaica KingstonJM, 1986)
Examines current food demand and supply in Jamaica. Discusses within the context of trends in food production and imports, as well as within the framework of existing policies and programs, their prospects for the 1986-1990 period. Suggests measures which could be introduced to ensure greater food and nutrition security for the population. Concludes with a discussion on the requirements of a food strategy, and suggestions for future action.